Cardiac Status of Patients with Thalassemia Major on Echocardiography - Tufail Ahmed Soomro, Rizwana Qureshi, Bela Bashir, Muhammad Zaki, Zuhaib Zahoor Soomro, Masnoor Ahmed Bouk (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Beta-thalassemia is a common genetic disorder in which red blood cell fail to perform normal function due to alterations in structure of red blood cells. Objective: To determine the cardiac status (mean left ventricular end diastolic diameter, left ventricular end systolic diameter and interventricular septal thickness) of patients with thalassemia major on echocardiography. Study Design: Cross-sectional study. Place and Duration of Study: Department of Pediatric Medicine, GMMMC Hospital, Sukkur from 2nd October 2020 to 1stApril 2021. Methodology: Ninety eight patients of both genders with age 2-18 years having thalassemia major. Thalassemia major were assessed and demographic variables including age, gender, family history of cardiac diseases, socio-economic status, other comorbid condition, duration since diagnosis of thalassemia was determined. All patients were also assessed for cardiac status using echocardiography. Results: Mean age of patients was 7.73±5.01 years. Mean duration since diagnosis of thalassemia was 6.12±4.80 years. There were 65 (66.33%) males and 33 (33.67%) female patients. There were 18 (18.37%) patients having low, 52 (53.06%) middle and 28 (28.57%) high status. Family history of cardiac disease was found in 15 (15.31%) patients. Mean left ventricular end diastolic diameter was 38.42±3.75 mm, left ventricular end systolic diameter was 24.45±2.40 mm and interventricular septal thickness was 6.23±1.45 mm. Conclusion: Left ventricular diastolic dysfunction (LVDD) occurs in all studied patients of thalassemia major. There was no systolic dysfunction and intraventricular septal thickening in thalassemia major patients. Keywords: Left ventricular end diastolic diameter, Left ventricular end systolic Diameter, Interventricular septal thickness, Thalassemia major, Echocardiography.